Handedness in surgical education: Evaluating suturing proficiency among left- and right-handed trainees - Elio R. Bitar; Joelle Hassanieh; Salim Rahhal; Batoul Zaiter; Ahmad Zaghal (Surgery Open Science)
Background: Left-handedness is often perceived as a disadvantage in surgical training due to the predominance of right-handed instruments and right-handed mentors. Whether this affects the performance of left-handed trainees remains unclear. This study aims to compare the suturing proficiency of left-handed and right-handed novice learners when taught by right-handed instructors using right-handed tools. Methods: A prospective, non-randomized, non-inferiority trial was conducted among students without prior suturing experience, divided by handedness. Participants underwent a teaching session on simple interrupted suturing using right-handed instruments and were assessed using a validated ten-item checklist. Secondary outcomes included satisfaction and were assessed via subjective questionnaires. Results: Among 129 participants (86 right-handed, 43 left-handed), no significant difference in suturing performance was observed between groups. However, left-handed participants reported subjective difficulties using right-handed instruments, and instructors noted challenges teaching them. Conclusion: Handedness does not impact the final outcome of basic surgical skills teaching. However, left-handed students may perceive more challenges due to right-handed tools and techniques. Tailoring teaching strategies and providing hand-specific tools may improve their learning experience.